Pengaruh E-Commerce, Digital Marketing, Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Generasi Z di Jakarta - Nurhayaty, Ety; Farman, Fanji; Wahyono, Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research was to determine the influence of e-commerce, digital marketing, entrepreneurial knowledge on generation Z's entrepreneurial interest. This research uses a quantitative approach. The population in this study is generation Z who are currently studying at high school and university levels in Jakarta. The sample used in this research was 93 respondents. Based on the partial results of the research, it is stated that there is a positive and significant influence of e-commerce on interest in entrepreneurship, digital marketing has a positive and significant influence on interest in entrepreneurship, and entrepreneurial knowledge has a positive and significant influence on interest in entrepreneurship. Simultaneous research results show that e-commerce, digital marketing, entrepreneurial knowledge have a positive and significant effect on generation Z's entrepreneurial interest in Jakarta Province. The coefficient of determination value is 0.576 or 57.6%. The results of these calculations mean that e-commerce, digital marketing, entrepreneurial knowledge influence interest in entrepreneurship by 57.6% while the remaining 42.4% is influenced by other factors not examined in this research.